2014
DOI: 10.1371/journal.pone.0085282
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Antagonistic Effects of Salinity and pH on Germination in Switchgrass (Panicum virgatum L.)

Abstract: The effects of salt-alkaline mixed stress on switchgrass were investigated by evaluating seed germination and the proline, malondialdehyde (MDA) and soluble sugar contents in three switchgrass (Panicum virgatum L.) cultivars in order to identify which can be successfully produced on marginal lands affected by salt-alkaline mixed stress. The experimental conditions consisted of four levels of salinity (10, 60, 110 and 160 mM) and four pH levels (7.1, 8.3, 9.5 and 10.7). The effects of salt-alkaline mixed stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
7
21
0
Order By: Relevance
“…Salinity stress-responsive genes identified here were in concurrence with an earlier study in switchgrass (Liu et al 2014) and included: ABC transporter family proteins, multidrug resistance-associated proteins, general control non-repressible, non-intrinsic ABC proteins, NSP-interacting kinases, and P-glycoproteins. Importantly, the unique salt stress-responsive genes identified in this study were aldehyde dehydrogenase, PHE ammonia-lyase, plasma membrane intrinsic protein, NOD26-like intrinsic protein, and tonoplast intrinsic proteins, which have been reported in rice and sorghum (Liu et al 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Salinity stress-responsive genes identified here were in concurrence with an earlier study in switchgrass (Liu et al 2014) and included: ABC transporter family proteins, multidrug resistance-associated proteins, general control non-repressible, non-intrinsic ABC proteins, NSP-interacting kinases, and P-glycoproteins. Importantly, the unique salt stress-responsive genes identified in this study were aldehyde dehydrogenase, PHE ammonia-lyase, plasma membrane intrinsic protein, NOD26-like intrinsic protein, and tonoplast intrinsic proteins, which have been reported in rice and sorghum (Liu et al 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Irrigation water D resulted in significantly lower above and below ground rapeseed biomass yields when compared to treatment C, a result attributed to the greater TOC concentration (salinity concentrations were equal, Table 7). This observation can be explained as the higher concentration of produced water organic compounds in irrigation water D resulted in higher cell damage of plants species, higher leaf EL, and less growth rate and is confirmed in literature (Bilgili et al, 2011;Francois et al, 1994;Liu et al, 2014).…”
Section: 31plant Growth and Biomass Yieldsupporting
confidence: 73%
“…Previous studies have indicated that switchgrass populations may show different responses to salt, such as a selective exclusion from the roots, as well as the accumulation of salts in aerial plant parts [23]. Increases in organic solutes (i.e., proline and soluble sugars), often related to salt tolerance, have also been found in response to increasing salt concentrations in switchgrass [26,27]. Other mechanisms, for example the elimination of salt through salt glands [22,28], have also been suggested, but in general information on the mechanisms and/or variability of salt tolerance among switchgrass genotypes is limited.…”
Section: Introductionmentioning
confidence: 99%